IgA anti-citrullinated protein antibodies are associated with flares during DMARD tapering in rheumatoid arthritis. - Sokolova, Maria; Hagen, Melanie; Bang, Holger; Schett, Georg; Rech, Jürgen; Steffen, Ulrike (Rheumatology, 2022)
OBJECTIVES: A substantial proportion of RA patients flare upon withdrawal of DMARDs, and thus the definition of prognostic markers is crucial. ACPA positivity has been identified as a risk factor for flare. However, only the role of IgG ACPA is established in this context, while the role of IgA ACPA is poorly defined. We thus aimed to investigate the role of IgA ACPA in flaring of RA. METHODS: Serum levels of IgA1 and IgA2 ACPA at baseline and after 12 months were measured in 108 patients from the randomized controlled RETRO study. RA patients in stable remission for at least 6 months at study recruitment were assigned to either one of the DMARD tapering arms or to continuation of DMARDs. RESULTS: In patients remaining in remission but not in the ones who flared, IgA2 ACPA levels and proportion of IgA2 in ACPA (IgA2% ACPA) significantly declined (median of 17.5%; P < 0.0001). This seemed to be independent of the treatment choice, as there was no difference in IgA2 ACPA dynamics between the study arms. IgA2% ACPA was associated with disease activity (DAS28) at flare (r = 0.36; P = 0.046). IgA and IgG ACPA showed a tendency towards independent contribution to the risk of flare with the highest risk if a patient had both antibody classes. CONCLUSION: In this study, IgA ACPA was identified as a risk factor for flare in combination with IgG ACPA. IgA2 ACPA levels were associated with flare severity and declined in patients in stable remission.
EVALuna2:474284